Myeloid antigens in childhood lymphoblastic leukemia: clinical data point to regulation of CD66c distinct from other myeloid antigens - Kalina, Tomas; Vaskova, Martina; Mejstrikova, Ester; Madzo, Jozef; Trka, Jan; Stary, Jan; Hrusak, Ondrej (BMC cancer, 2005)
BACKGROUND: Aberrant expression of myeloid antigens (MyAgs) on acute lymphoblastic leukemia (ALL) cells is a well-documented phenomenon, although its regulating mechanisms are unclear. MyAgs in ALL are interpreted e.g. as hallmarks of early differentiation stage and/or lineage indecisiveness. Granulocytic marker CD66c -- Carcinoembryonic antigen-related cell adhesion molecule 6 (CEACAM6) is aberrantly expressed on ALL with strong correlation to genotype (negative in TEL/AML1 and MLL/AF4, positive in BCR/ABL and hyperdiploid cases). METHODS: In a cohort of 365 consecutively diagnosed Czech B-precursor ALL patients, we analyze distribution of MyAg+ cases and mutual relationship among CD13, CD15, CD33, CD65 and CD66c. The most frequent MyAg (CD66c) is studied further regarding its stability from diagnosis to relapse, prognostic significance and regulation of surface expression. For the latter, flow cytometry, Western blot and quantitative RT-PCR on sorted cells is used. RESULTS: We show CD66c is expressed in 43% patients, which is more frequent than other MyAgs studied. In addition, CD66c expression negatively correlates with CD13 (p < 0.0001), CD33 (p = 0.002) and/or CD65 (p = 0.029). Our data show that different myeloid antigens often differ in biological importance, which may be obscured by combining them into "MyAg positive ALL". We show that unlike other MyAgs, CD66c expression is not shifted from the onset of ALL to relapse (n = 39, time to relapse 0.3-5.3 years). Although opposite has previously been suggested, we show that CEACAM6 transcription is invariably followed by surface expression (by quantitative RT-PCR on sorted cells) and that malignant cells containing CD66c in cytoplasm without surface expression are not found by flow cytometry nor by Western blot in vivo. We report no prognostic significance of CD66c, globally or separately in genotype subsets of B-precursor ALL, nor an association with known risk factors (n = 254). CONCLUSION: In contrast to general notion we show that different MyAgs in lymphoblastic leukemia represent different biological circumstances. We chose the most frequent and tightly genotype-associated MyAg CD66c to show its stabile expression in patients from diagnosis to relapse, which differs from what is known on the other MyAgs. Surface expression of CD66c is regulated at the gene transcription level, in contrast to previous reports.
Keywords: antigen Lewis X; Immunophenotyping; průtoková cytometrie; imunofenotypizace; genotyp; Sialic Acid Binding Ig-like Lectin 3; kojenec; Prognosis; Time Factors; regulace genové exprese u nádorů; antigeny diferenciační myelomonocytární; Česká republika; mladiství; Cell Membrane; CD13 Antigens; Cohort Studies; akutní lymfatická leukemie; Genotype; Lewis X Antigen; GPI-Linked Proteins; Infant; recidiva; Adolescent; Czech Republic; kohortové studie; Antigens, Differentiation, Myelomonocytic; glykosylace; dítě; RNA; genetická transkripce; western blotting; GPI-vázané proteiny; polymerázová řetězová reakce s reverzní transkripcí; Child; Flow Cytometry; antigen CD33; Child, Preschool; Blotting, Western; Glycosylation; Disease-Free Survival; cytoplazma; prognóza; Humans; předškolní dítě; Gene Expression Regulation, Neoplastic; Recurrence; Antigens, CD; časové faktory; antigeny CD13; buněčná membrána; Reverse Transcriptase Polymerase Chain Reaction; Cytoplasm; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Transcription, Genetic; molekuly buněčné adheze; CD antigeny; přežití bez známek nemoci; lidé; Cell Adhesion Molecules